The contemporary refugee crisis: an overview of mental health challenges. Issue 2 (June 2017) - Silove, Derrick; Ventevogel, Peter; Rees, Susan
Abstract : There has been an unprecedented upsurge in the number of refugees worldwide, the majority being located in low‐income countries with limited resources in mental health care. This paper considers contemporary issues in the refugee mental health field, including developments in research, conceptual models, social and psychological interventions, and policy. Prevalence data yielded by cross‐sectional epidemiological studies do not allow a clear distinction to be made between situational forms of distress and frank mental disorder, a shortcoming that may be addressed by longitudinal studies. An evolving ecological model of research focuses on the dynamic inter‐relationship of past traumatic experiences, ongoing daily stressors and the background disruptions of core psychosocial systems, the scope extending beyond the individual to the conjugal couple and the family. Although brief, structured psychotherapies administered by lay counsellors have been shown to be effective in the short term for a range of traumatic stress responses, questions remain whether these interventions can be sustained in low‐resource settings and whether they meet the needs of complex cases. In the ideal circumstance, a comprehensive array of programs should be provided, including social and psychotherapeutic interventions, generic mental health services, rehabilitation, and special programs for vulnerable groups. Sustainability of services, ensuring best practice, evidence‐based approaches, and promoting equity of access must remain the goals of future developments, a daunting challenge given that most refugees reside in settings where skills and resources in mental health care are in shortest supply.